FARINHA MISTA DE TRIGO E BOCA´´IUVA: QUALIDADE TECNOLÓGICA E VIDA DE PRATELEIRA - OLIVEIRA, Letícia da Silva; DONADON, Juliana Rodrigues; HIANE, Priscila Aiko; GUIMARÃES, Rita de Cassia Avellaneda (ANAIS DO ENIC, 2023)
-